Strategi dan Teknik Penulisan Artikel Ilmiah untuk Publikasi pada Jurnal Terindeks SINTA 2 - Putro, Muhammad Wachid Suryo; Hayadi, B.Herawan; Apriyudin, Apriyudin; Haryati, Reti Sri; Nurlina, Nina; Hisaanah, Khauranina (STAI Darul Qalam Tangerang, 2026)
Scientific publication is an essential part of academic activities as it serves as a medium for disseminating research findings to a broader scientific community. In Indonesia, the quality of scientific journals is assessed, among others, through the Science and Technology Index (SINTA) system managed by the Ministry of Education, Culture, Research, and Technology. Journals ranked in SINTA 2 are categorized as reputable national journals with relatively strict selection standards. Therefore, authors need to understand effective scientific writing techniques to increase their chances of being published in such journals. This article aims to examine various strategies for writing scientific articles that are effective and aligned with the standards of reputable journal publications. The method used is a literature study by reviewing various research methodology books and relevant scientific journal articles. The results of the study indicate that the success of scientific publication is influenced by several important factors, including the selection of relevant research topics, the use of up-to-date scientific references, the organization of a systematic article structure, and the author’s ability to demonstrate research novelty. In addition, understanding journal writing guidelines and academic ethics is also a crucial factor in the publication process. By understanding these strategies, authors are expected to be able to produce high-quality scientific articles with a greater chance of being accepted in SINTA 2 indexed journals.